Arend Lijphart, Patterns of democracy. Government forms and performance in thirty-six countries - Γεωργιάδου, Βασιλική (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2015)
[Δεν διατίθεται περίληψη / no abstract available]